Skador av hasch och marijuana - Ramström, Jan (Socialmedicinsk tidskrift, 2007)
Under de senaste 10 åren har intresset - mätt i per år publicerade vetenskapliga studier - för cannabis skadeverkningar ökat påtagligt. Speciellt inom området psykiatriska och psykosociala (inklusive försämrad förmåga att framföra motorfordon) skador har allt fler orsakssamband mellan cannabisrökning och sjukdomar och funktionsnedsättningar kunnat fastställas. Kännedom om cannabis skadeverkningar har stor betydelse för de åtgärder, alltifrån narkotikapolitiska - som man vidtar i ett folkhälsoperspektiv - till behandling som man riktar till den enskilde missbrukaren. There is a growing interest in cannabis-related questions over the past ten years - the number of scientific publications per year has grown strongly. Among researchers and clinicians it has become more common to make concerned statements over the current situation, the most important reason for this uneasiness is the increase in studies confirming previously suspected or proven psychological, psychosocial and physical harmful consequences of cannabis abuse. The article sums up the state of knowledge regarding the harmful effects of cannabis. There is an exception for psychosis and related states, problems which are discussed in the article of Peter Allebeck in this issue of Socialmedicinsk tidskrift. The article is somewhat of an abbreviation of the report Adverse Health Consequences of cannabis use, published by National Institute of Public Health – Sweden. In this report you can also find a complete list of references. Internet address:www.fhi.se